Review of the Book "Local History of Iran in the Islamic Period until the Seventh Century AH" - Morteza Nouraei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book, "Local History of Iran in the Islamic Period until the Seventh Century AH" (Qanavat, 2013, pp 434), includes historical concepts that rely on the flow of text-writing in the field of history, the history of text-in-text. In other words, the end-mean is not a representation of historical events or events either, but rather the reconstruction of a specific historiography -local- in the process of the period from the third to the seventh AH. The evolution of local historiography from monog raphs such as fotoh and kharaj, to the biographies of tabaqat and rejal and their entry to the local history papers, including the transition process of the trend in this era are all under study. Therefore, the present book attempts to reveal a trend in the method and meaningful method of historiographical retrospective. Did the writers have consciousness on the nature and kind of their writings? The approach in this book, with which the writer has fallen deep into the depths of the book, seeks to revise it, which is in fact, a glimpse into the past of the locality, following the main question on local history through sources. The process of creation sources revealed a rich tradition in order to preserve the past time in the texts. Therefore, the process of reconstructing and reviewing texts in the form of finding main elements in the method and perspective has in fact been able to show the rich tradition of local historiography in Iran during the medieval period. This book illustrates the evolutionary trend of local historiography in Iran until the seventh century. The fundamental premise of this book is that time, geography (place), and political systems are triangles of transition in local historiography.